(untitled) (Journal of Population and Development, 2021)
Spousal violence is a major public health phenomenon. It is a hidden issue in Nepal especially in rural areas. The objective of this study is to explore the prevalence and associated risk factors of spousal violence in rural Nepal. For this study, the data has been imported from Nepal Demographic and Health Survey (NDHS), 2016. This study is confined in 1510 married women from rural Nepal. Bivariate analysis and logistic regression has been applied to examine the association between variables. Study found that more than half of the respondents were 25 to 34 years aged and the overwhelming majority were (87%) Hindu. Study showed that half of the respondents had no education while 19 percent of respondents’ husbands had no education. More than a fifth (24%), more than a tenth (13%) and about a tenth (8%) had ever experienced physical, emotional and sexual violence respectively. Four in one (28%) women experienced at least one form of violence while 3 percent experienced all three forms of violence. Education of women, education of husbands and consumption of alcohol were highly associated with spousal violence. Women who had no education were 1.7 times more likely to experience violence than higher education. Likewise, other variables for example, age at first marriage, husbands’ education, consumption of alcohol and own financial account were also associating factors of spousal violence in rural Nepal. So that, attention should stand towards rural Nepal’s education for both men and women, excessive consumption of alcohol, upgrade the level of empowerment of women to mitigate intimate partner violence.